Visual Discrimination, Serial Reversal, and Extinction Learning in the mdx Mouse - Dickson, Price E.; Mittleman, Guy (Frontiers in Behavioral Neuroscience, 2019)
Duchenne muscular dystrophy (DMD) is the most common form of muscular dystrophy and the most common neuromuscular disorder. In addition to neuromuscular consequences, some individuals with DMD experience global intellectual dysfunction and executive dysfunction of unknown mechanistic origin. The cognitive profile of the mdx mouse, the most commonly used mouse model of DMD, has been incompletely characterized and has never been assessed using the touchscreen operant conditioning paradigm. The touchscreen paradigm allows the use of protocols that are virtually identical to those used in human cognitive testing and may therefore provide the most translational paradigm for quantifying mouse cognitive function. In the present study, we used the touchscreen paradigm to assess the effects of the mdx mutation on visual discrimination learning, serial reversal learning, and extinction learning. To enable measuring task-dependent learning and memory processes while holding demands on sensory-driven information processing constant, we developed equally salient visual stimuli and used them on all experimental stages. Acquisition of the initial pairwise visual discrimination was facilitated in mdx mice relative to wildtype littermates; this effect was not explained by genotypic differences in impulsivity, motivation, or motor deficits. The mdx mutation had no effect on serial reversal or extinction learning. Together, findings from this study and previous studies suggest that mdx effects on cognitive function are task specific and may be influenced by discrimination type (spatial, visual), reward type (food, escape from a non-preferred environment), sex, and genetic background.